Performance and mineral metabolism of broiler replacing commercial diet by rice polish and supplementation of citric acid - Islam, KMS; Debi, MR; Liesegang, A (Bangladesh Journal of Animal Science, 2021)
During an experimental period of 28 days citric acid (CA) was tested as a growth promoter instead of antibiotics with replacement of commercial diet by rice polish (RP). Newly 240 hatched broiler chicks (Cobb 500) distributed into eight dietary groups (3 replicate cages having 10 birds in each), 1=Control (commercial diet), 2=Commercial diet+0.5% CA, 3=5.0% RP, 4=5.0% RP+ 0.5% CA, 5=10.0% RP, 6=10.0% RP+0.5% CA, 7=15.0% RP, 8=15.0% RP+0.5% CA. Diets were supplemented by acid insoluble ash (1.0% Celite) as marker. At the end, blood sample was collected from all birds. Total ash, mineral content and density of tibia were determined. Final body weight (g/b) of chicks were 1655, 1733, 1642, 1694, 1618, 1656, 1613 and 1631 g, respectively (P>0.05). Feed intake (g/bird) was 2359, 2419, 2432, 2433, 2524, 2494, 2519 and 2424 g, respectively (P>0.05). FCR varied (P<0.05) among the groups were 1.48, 1.44, 1.54, 1.49, 1.62, 1.55, 1.62 and 1.54, where better FCR was in CA groups comparison to non-CA groups. Retention of Ca, P and Mg increased in CA group’s comparison to non-CA groups but replacement of 5.0% commercial diet (with or without CA) caused higher retention level. Higher dressing percentage observed in CA group (65.4, 65.9 for group 2, 4) comparison to non-CA groups (63.8, 63.9 for groups 1, 3). Bone mineral concentration (total ash, Ca, P and Mg) slightly increased in CA groups (P>0.05). In general, replacement of a commercial diet by RP up to 15.00% would be possible maintaining growth performance of broiler where further supplementation of 0.5% CA showed more advantages by increasing mineral density of bone. Bang. J. Anim. Sci. 2020. 49 (2): 159-165